Clinical Efficacy and Safety of Buzhong Yiqi Decoction in Treating Epigastric Pain: A Systematic Review and Meta-Analysis - Miao, Jiajing (Transactions on Computer Science and Intelligent Systems Research, 2024)
Epigastric pain is the most common digestive tract symptom in clinical practice without good treatment to intervene at present. Buzhong Yiqi decoction (BYD) is a relatively common traditional Chinese medicine for the treatment of digestive tract diseases now, which can yiqi in the spleen and stomach. Hence, this study aims to explore the clinical efficacy and safety of BYD in the treatment of epigastric pain, so as to provide a reference for the clinical treatment of epigastric pain in the future. Randomized controlled trials of BYD in treating epigastric pain are investigated by searching common databases in Chinese and English. Meta-analysis is conducted by RevMan 5.4. According to the results, compared with the western pharmaceutic treatment, BYD could improve the clinical efficacy of epigastric pain (OR = 4.14, 95% CI [3.22, 5.33], P < 0.00001) and mitigate symptoms such as belching (MD = -0.82, 95% CI [-1.15, -0.49], P < 0.00001), insufficient appetite (MD = -0.49, 95% CI [-0.65, -0.33], P < 0.00001), nausea and vomiting (MD = -0.34, 95% CI [-0.48, -0.19], P < 0.00001), abdominal distension (MD = -0.38, 95% CI [-0.55, -0.20], P < 0.0001), fullness (MD = -0.51, 95% CI [-0.59, -0.43], P < 0.00001) and anorexia (MD = -0.59, 95% CI [-0.70, -0.48], P < 0.00001). Meanwhile, BYD could promote quality of life (MD = 7.45, 95% CI [3.91, 10.99], P < 0.0001) and reduce the adverse reaction incidence (OR = 0.27, 95% CI [0.13, 0.53], P = 0.0002). The results show that the treatment of epigastric pain with BYD has significant clinical effects and strong safety, which can be applied to clinical use.